Long‐term survival outcomes of patients with Niemann‐Pick disease type C receiving miglustat treatment: A large retrospective observational study. Issue 5 (8th May 2020) - Patterson, Marc C.; Garver, William S.; Giugliani, Robert; Imrie, Jackie; Jahnova, Helena; Meaney, F John; Nadjar, Yann; Vanier, Marie T.; Moneuse, Patrick; Morand, Olivier; Rosenberg, Daniel; Schwierin, Barbara; et al.
Abstract: Miglustat has been indicated for the treatment of Niemann‐Pick disease type C (NP‐C) since 2009. The aim of this observational study was to assess the effect of miglustat on long‐term survival of patients with NP‐C. Data for 789 patients from five large national cohorts and from the NPC Registry were collected and combined. Miglustat‐treated and untreated patients overall and within sub‐groups according to age‐at‐neurological‐onset, that is, early infantile‐onset (<2 years), late infantile‐onset (2 to <6 years), juvenile‐onset (6 to <15 years), and adolescent/adult‐onset (≥15 years) were analysed and compared. Survival was analysed from the time of first neurological manifestation (Neurological onset group, comprising 669 patients) and from diagnosis (Diagnosis group, comprising 590 patients) using a Cox proportional hazard model adjusted for various covariates. Overall, 384 (57.4%) patients in the Neurological onset group and 329 (55.8%) in the Diagnosis group were treated with miglustat. Miglustat treatment was associated with a significant reduction in risk of mortality in both groups (entire Neurological onset group, Hazard ratio [HR] = 0.51; entire Diagnosis group, HR = 0.44; both P < .001). The effect was observed consistently in all age‐at‐neurological‐onset sub‐groups (HRs = 0.3 to 0.7) and was statistically significant for late infantile‐onset patients in both groups (Neurological onset group, HR = 0.36, P < .05; Diagnosis group, HR = 0.32, P < .01), and juvenile‐onset patients in the Diagnosis group only (HR = 0.30, P < .05). Despite the limitations of the data that urge cautious interpretation, the findings are consistent with a beneficial effect of miglustat on survival in patients with NP‐C. Abstract :